Rituximab in patients with acute ST-elevation myocardial infarction (RITA-MI). (25th November 2020) - Zhao, T.X; Aetesam-Ur-Rahman, M; Sage, A; Lu, Y; Victor, S; Kurian, R; Fielding, S; Hoole, S.P; Mallat, Z
Abstract: Background: In pre-clinical models of acute myocardial infarction (MI), mature B cells selectively mobilise inflammatory monocytes into the heart, leading to increased infarct size and deterioration of myocardial function. Anti-CD20 antibody-mediated depletion of B cells limited infarct size and improved cardiac function. Rituximab is a monoclonal antibody targeted against human B cells and has been used in the treatment of autoimmune diseases and cancers. However, its use in cardiovascular disease is untested and is currently contraindicated. Purpose: We assessed the safety, feasibility and pharmacodynamic effect of rituximab given acutely to patients with ST-elevation MI (STEMI). Method: RITA-MI was a prospective, open-label, dose-escalation, single-arm, phase 1/2a clinical trial, which tested rituximab administered as a single intravenous dose in patients with STEMI within 48 hours of symptom onset. Four escalating doses (200, 500, 700 and 1000mg) were used with 6 patients in each group. Follow-up was performed during initial inpatient stay; on days 6 and 14; and at 3 and 6 months. The primary endpoint was safety, whilst secondary endpoints were changes in B cells and their subsets, immune cell subsets, and cardiac and inflammatory biomarkers. [NCT:03072199] Results: Overall, rituximab was well tolerated across all doses with the most common adverse event being gastrointestinal disturbance. This was due to the concomitant oral secondary prevention medication started after a STEMI. Five severe adverse events were reported, none of which were assessed as being related. Rituximab caused a mean 96.3% (95% CI 93.8–98.8%) depletion of B cell within 30 mins of the infusion starting across all dose groups. At 6 hours a rebound in B cells was seen in the 200, 500 and 700mg doses, likely related to the emigration of B cells from secondary lymphoid tissues. Maximal B cell depletion was seen at day 6, which was lower than baseline for all doses (p<0.001) (figure 1). B cell repopulation at 6months was dose-dependent. In addition, there was modulation of returning B cell subsets characterised by increased transitional B cells (figure 1C). Immunoglobulin (IgG, IgM and IgA) levels were not affected during follow-up. Rituximab also caused an acute and transient decrease in lymphocytes (both CD4+ and CD8+ T cells) and monocytes, whilst transiently increasing neutrophils at the 6-hour timepoint. Cardiac biomarkers showed a decrease in CRP and BNP. Clinical echocardiogram showed an increase in ejection fraction at follow up (mean increase in EF of 7.8% (95% CI 3.11–12.6)). Conclusion: Rituximab appears safe and feasible when given in acute STEMIs. We have shown for the first time that depletion of B cells within 30mins of starting rituximab which demonstrates the biological plausibility of our treatment paradigm. Additional new insight into the mechanism of action of rituximab was found. This has led directly to the setting up of a phase 2b trial. Funding Acknowledgement: Type of funding source: Public grant(s) – EU funding. Main funding source(s): European Union Research Council